HLA-DR Expression on Monocyte Subsets in Critically Ill Children. Issue 10 (October 2018) - Boeddha, Navin P.; Kerklaan, Dorian; Dunbar, Albert; van Puffelen, Esther; Nagtzaam, Nicole M. A.; Vanhorebeek, Ilse; Van den Berghe, Greet; Hazelzet, Jan A.; Joosten, Koen F.; Verbruggen, Sascha C.; Dik, Willem A.; Driessen, Gertjan J.
Abstract : Background: To longitudinally study blood monocyte subset distribution and human leukocyte antigen-DR (HLA-DR) expression on monocyte subsets in children with sepsis, post-surgery and trauma in relation to nosocomial infections and mortality. Methods: In 37 healthy children and 37 critically ill children (12 sepsis, 11 post-surgery, 10 trauma and 4 admitted for other reasons)—participating in a randomized controlled trial on early versus late initiation of parenteral nutrition—monocyte subset distribution and HLA-DR expression on monocyte subsets were measured by flow cytometry upon admission and on days 2, 3 and 4 of pediatric intensive care unit (PICU) stay. Results: Upon PICU admission, critically ill children had a higher proportion of classical monocytes (CD14++CD16−) than healthy children [PICU 95% (interquartile range [IQR] 88%–98%); controls, 87% (IQR 85%–90%), P < 0.001]. HLA-DR expression was significantly decreased within all monocyte subsets and at all time points, being most manifest on classical monocytes and in patients with sepsis. Percentage of HLA-DR expressing classical monocytes [upon PICU admission 67% (IQR 44%–88%); controls 95% (IQR 92%–98%), P < 0.001], as well as the HLA-DR mean fluorescence intensity [upon PICU admission 3219 (IQR 2650–4211); controls 6545 (IQR 5558–7647), P < 0.001], decreased during PICU stay. Patients who developed nosocomial infections ( n = 13) or who died ( n = 6) had lower HLA-DR expression on classical monocytes at day 2 ( P = 0.002) and day 3 ( P = 0.04), respectively. Conclusions: Monocytic HLA-DR expression decreased during PICU stay and was lower compared with controls on all examined time points, especially on classical monocytes and in children admitted for sepsis. Low HLA-DR expression on classical monocytes was associated with nosocomial infections and death. Abstract : Supplemental Digital Content is available in the text.